Iron-silicon core-shell type hydrocracking catalyst as well as preparation method and application thereof

By adopting the iron-silicon core-shell hydrocracking catalyst, the core structures of iron oxide and transition metals and the shell structures of silica and silicon dioxide are used, combined with mesoporous channels, the existing catalysts have been solved, and the cost of high efficiency has been achieved. Residue conversion and low coke yield have good industrial application prospects.

CN119455946APending Publication Date: 2025-02-18XINJIANG AGRI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411619651.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing suspension bed hydrocracking catalysts have poor catalytic activity, unstable properties, low raw material conversion and liquid yield, high coke yield, large load of active metals, and high production costs.

Method used

The iron-silicon core-shell hydrocracking catalyst is used, and its core includes iron oxide and transition metal. The silica shell contains mesoporous channels. It is prepared by specific preparation methods, including iron salt, transition metal salt and water, sodium acetate, The mixture reaction of cetyltrimethylammonium bromide and ethylenediamine is followed by washing, drying, calcining and other steps.

Benefits of technology

It improves the catalytic activity and stability of the catalyst, increases the residual oil conversion rate, reduces the yield of gas and coke, increases the yield of naphtha and middle distillate oil, and has low production costs and has good industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455946A_ABST
    Figure CN119455946A_ABST
Patent Text Reader

Abstract

The invention discloses an iron-silicon core-shell type hydrocracking catalyst as well as a preparation method and application thereof, and belongs to the technical field of catalytic material preparation and energy. The catalyst is a core-shell type catalyst with iron oxide as a core and silicon dioxide as a shell, VIB and / or VIII group transition metal is doped in the core, and mesoporous channels are constructed on the shell. The preparation method comprises the following steps: preparing a spherical metal catalytic material from ferric salt and transition metal salt as raw materials, and adding a silicon source to prepare the iron-silicon core-shell type hydrocracking catalyst. When the catalyst is applied to a residual oil suspended bed hydro-conversion process, the core-shell structure in the catalyst can reduce the agglomeration effect of metal oxides, and the pore channels of the silicon layer can improve the dispersity of the catalyst and the accessibility of residual oil and active components and promote the hydrogenation effect of the catalyst, so that the conversion rate of the residual oil in a suspended bed hydro-cracking reaction is up to about 90%; the total yield of naphtha and middle distillate can reach 60%, the yield of gas and coke is low, and the method has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic material preparation and energy, and specifically relates to an iron silicon core-shell type hydrocracking catalyst and a preparation method and application thereof. Background Art

[0002] Under strict environmental regulations, renewable energy is growing in order to reduce carbon dioxide emissions. However, fossil fuels will remain very important to meet the huge global energy demand in the coming decades. Therefore, with the increasing depletion of conventional oil, the efficient use of inferior heavy oil to produce clean transportation fuels has received widespread attention. Residue oil is the heaviest fraction in crude oil, accounting for about 40-60%. It is mainly composed of polycyclic aromatic hydrocarbons and contains a large amount of sulfur (S), nitrogen (N), vanadium (V), nickel (Ni) and other metals. During the processing, the catalyst is often deactivated due to coking and metal deposition. Therefore, it is very challenging to efficiently convert residue oil into light fractions. Among the several hydrocracking / hydroprocessing technologies currently under development, suspended bed hydrocracking technology is considered to be the most effective and economical process due to its large feedstock flexibility, high conversion efficiency and high light fraction yield.

[0003] In order to increase the yield of light oil products and reduce the yield of by-product gas and coke, people have conducted a lot of research on the development of suspended bed hydrocracking catalysts. Suspended bed hydrocracking catalysts include homogeneous oil-soluble dispersed catalysts, water-soluble dispersed catalysts and heterogeneous solid powder catalysts. Among them, oil-soluble and water-soluble dispersed catalysts have high hydrogenation activity, but their application in the oil refining industry is limited due to disadvantages such as high production cost and complex operation. Natural mineral catalysts, as solid powder catalysts, have the advantages of low cost and wide sources, and have been widely used in the early stage of suspended bed hydrocracking technology. However, due to their low catalytic activity and unstable properties, they have been gradually replaced by supported metal catalysts. For example, Fe natural powder catalysts have been adopted in the early stage of the development of suspended bed hydrocracking technology due to their low cost and wide sources, but their catalytic hydrogenation activity is poor and cannot meet the requirements of high yield of light fractions and inhibition of coke formation. Therefore, the use of cheap metal Fe combined with a carrier to prepare a high-performance hydrocracking catalyst will provide a strong guarantee for the industrialization of residue oil upgrading. Compared with natural mineral catalysts, supported metal catalysts have the advantages of improving the activity of hydrocracking reactions and adjustable performance, so they are increasingly valued in suspended bed hydrocracking reactions.

[0004] Supported metal catalysts are composed of active metals and carriers, where the active metals are usually Mo, Co, Ni or their binary / ternary combinations, which are the active centers for hydrogenation; the carriers are usually acidic substances, such as Al2O3, ASA, zeolites or natural minerals, which play a cracking role in the catalytic reaction. Numerous studies have shown that the matching of active metals and carriers affects the composition, pore structure and acidity of the catalyst, which in turn affects the catalytic performance. At present, supported catalysts still have problems such as low raw material conversion rate and liquid yield, high coke yield, large active metal loading, and high production cost, which restrict the industrial application of this type of catalyst.

[0005] The prior art discloses an iron-molybdenum suspension bed hydrocracking catalyst and a preparation method thereof, which is used to convert heavy hydrocarbon raw materials into light hydrocarbon products. The catalyst mainly comprises two parts, iron and molybdenum, and aluminum is used as the third catalytic component. The content of Mo in the reaction is about 500ppm, the mass fraction of iron is 5 times that of Mo, and the conversion rate of heavy hydrocarbons is about 85%. The prior art also discloses that waste wood powder is used as a template to successfully synthesize mesoporous iron oxide and evaluate its activity in the residual oil suspension bed hydrocracking reaction. The results show that the gasoline and diesel fractions of mesoporous alumina with a large specific surface area and pore volume have a high yield of about 50wt%, a coke yield of 2wt%, and a gas yield of 20wt%. Overall, the hydrogenation activity of iron oxide catalysts has been greatly improved, but it is not enough to achieve the purpose of inhibiting the production of coke and gas, resulting in a low yield of liquid oil products. However, metal iron oxides are prone to metal aggregation reactions, resulting in catalyst deactivation and more coke. Therefore, the morphology of the catalyst has a great influence on the catalyst. Core-shell structure catalysts have excellent application performance due to their unique structure and morphology. For example, researchers used shear-assisted interfacial co-assembly technology to synthesize a composite catalyst with iron oxide as the core and silicon dioxide as the shell in a n-hexane / water two-liquid system, which showed good application performance in biocatalysis. Researchers used hydrothermal method, Methyl-modified Fe2O3@SiO2 core-shell catalysts were prepared by silylation reaction, in which the SiO2 shell served as a bridge connecting the iron core and the CH3 hydrophobic group to obtain a highly hydrophobic iron-based catalyst, which showed high CO hydrogenation reaction activity and stability. Summary of the invention

[0006] In view of the above-mentioned prior art, the present invention discloses an iron-silicon core-shell type hydrocracking catalyst and a preparation method and application thereof, so as to solve the technical problems in the prior art of suspended bed hydrocracking catalyst such as poor catalytic activity, unstable properties, low raw material conversion rate and liquid yield, high coke yield, large active metal loading and high production cost.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing an iron-silicon core-shell type hydrocracking catalyst, which comprises the following steps:

[0008] S1: mixing iron salt, VIB and / or VIII group transition metal salt, water, sodium acetate, hexadecyltrimethylammonium bromide and ethylenediamine to obtain a reaction solution, and reacting at 180-220° C. for 8-12 hours to obtain a colloid;

[0009] S2: washing the colloid to neutrality, and obtaining a spherical metal catalytic material after centrifugation and drying;

[0010] S3: Grind the spherical metal catalyst material, then evenly disperse the spherical metal catalyst material powder and hexadecyltrimethylammonium bromide in a solvent, add ammonia water, react at room temperature for 25 to 35 minutes, then add ethyl silicate to the reaction solution, react at room temperature for 5.5 to 6.5 hours, and after the reaction is completed, centrifuge, dry and calcine the reaction solution to obtain the product.

[0011] Based on the above technical solution, the present invention can also be improved as follows.

[0012] Furthermore, in step S1, the iron salt is one or more of ferric nitrate, ferric chloride, ferric sulfate, ferric phosphate, ferric perchlorate, ferric nitrate nonahydrate and ferric chloride hexahydrate.

[0013] Furthermore, in step S1, the VIB group transition metal salt is ammonium molybdate and / or metatungstic acid; the VIII group transition metal salt is one or more of nickel nitrate, nickel sulfide and cobalt nitrate.

[0014] Furthermore, the concentration of the iron salt in the reaction solution of step S1 is 50-70 g / L; the material-liquid ratio of the iron salt, VIB and / or VIII group transition metal salt, sodium acetate, hexadecyltrimethylammonium bromide and ethylenediamine is 3-8 mmol: 0.3-0.8 mmol: 7.5-10 mmol: 1 mmol: 4-11 mL.

[0015] Furthermore, in step S2, the centrifugal speed is 7500-85000 r / min, the centrifugal time is 5-6 min; the drying temperature is 80-150° C., and the drying time is 22-26 h.

[0016] Furthermore, the particle size of the spherical metal catalyst material powder is not less than 40 meshes; the solvent is a mixed solvent of ethanol and water, and the volume ratio of ethanol to water in the mixed solvent is 3-5:4-6; the concentration of ammonia water is 28wt%.

[0017] Furthermore, in step S3, the material-liquid ratio of the spherical metal catalyst material powder, hexadecyltrimethylammonium bromide, solvent, ammonia water and ethyl silicate is 0.5-1.5 g: 3.5-5.5 g: 700-1100 mL: 5-15 g: 1-10 g.

[0018] Furthermore, in step S3, the drying temperature is 80-150° C., and the drying time is 24-36 hours; the roasting temperature is 480-520° C., and the roasting time is 2-5 hours.

[0019] The iron-silicon core-shell type hydrocracking catalyst prepared by the preparation method has a core comprising iron oxide and VIB and / or VIII group transition metals, and a silicon dioxide shell containing mesoporous channels with a size of 5 to 12 nm.

[0020] The invention also discloses the application of the iron-silicon core-shell type hydrocracking catalyst in a residual oil suspension bed hydroconversion process.

[0021] The beneficial effects of the present invention are:

[0022] 1. The present invention uses low-cost inorganic iron salt as raw material to prepare the catalyst, which has simple preparation process, low production cost, green and environmental protection, and has good industrial application prospects.

[0023] 2. The core-shell catalyst prepared by the present invention has iron oxide as the core and silicon dioxide as the shell, the core is also doped with VIB or VIII group transition metals, and mesoporous channels are constructed on the shell; the core-shell structure can reduce the agglomeration effect of metal oxides, and the channels of the silicon layer can improve the dispersibility of the catalyst and the accessibility of residual oil and active components, thereby improving the catalytic activity.

[0024] 3. The catalyst prepared by the present invention is applied to the residual oil suspension bed hydrogenation conversion process, the residual oil conversion rate is as high as about 90%, the total yield of naphtha and middle distillate oil can reach 60%, and the gas and coke yields are relatively low. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the SEM image of the Co / Fe2O3@SiO2 core-shell catalyst prepared in Example 1;

[0026] Figure 2 This is the SEM image of the Ni / Fe2O3@SiO2 core-shell catalyst Ⅰ prepared in Example 2;

[0027] Figure 3 This is the SEM image of the Mo / Fe2O3@SiO2 core-shell catalyst prepared in Example 3. DETAILED DESCRIPTION

[0028] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.

[0029] Example 1

[0030] An iron-silicon core-shell type hydrocracking catalyst, the preparation method of which comprises the following steps:

[0031] S1: Add 6g Fe(NO3)3·9H2O, 0.27g cobalt nitrate and 70mL deionized water into a beaker, stir well, add 1.95g sodium acetate and 1g hexadecyltrimethylammonium bromide, then add 30mL ethylenediamine, stir well, transfer to a stainless steel autoclave with a polytetrafluoroethylene liner, and react at 200°C for 10h; after the reaction is completed, cool the autoclave to room temperature to obtain a red colloid;

[0032] S2: repeatedly washing the red colloid with deionized water until it is neutral, then centrifuging the red colloid at a centrifugal speed of 8000 r / min for 6 min, and then drying the solid matter obtained after centrifugation at 100° C. for 24 h to obtain a spherical metal catalytic material;

[0033] S3: Grind the spherical metal catalyst material and sieve it with a mesh size of 40, then take 1g of the sieved spherical metal catalyst material powder and 4.5g of hexadecyltrimethylammonium bromide and evenly disperse them in a mixed solvent of 900mL of ethanol and deionized water, and the volume ratio of ethanol to deionized water is 4:5, then add 10g of 28wt% ammonia water to the dispersion, and then react at room temperature for 30min, then add 4g of ethyl silicate to the reaction solution, and react at room temperature for 6h. After the reaction, centrifuge the reaction solution at a centrifugal speed of 8000r / min and a centrifugal time of 6min. Dry the solid after centrifugation at 100℃ for 24h, and then calcine at 500℃ for 5h to obtain Co / Fe2O3@SiO2 core-shell catalyst.

[0034] Example 2

[0035] An iron-silicon core-shell type hydrocracking catalyst, the preparation method of which comprises the following steps:

[0036] S1: Add 6g Fe(NO3)3, 1g nickel nitrate and 71mL deionized water into a beaker, stir well, add 7.68g sodium acetate and 4.5g hexadecyltrimethylammonium bromide, then add 49mL ethylenediamine, stir well, transfer to a stainless steel autoclave with a polytetrafluoroethylene liner, and react at 180°C for 8h; after the reaction is completed, cool the autoclave to room temperature to obtain a red colloid;

[0037] S2: The red colloid is repeatedly washed with deionized water until it is neutral, and then the red colloid is centrifuged at a centrifugal speed of 7500 r / min for 5 min. The solid matter obtained after the centrifugation is then dried at 80° C. for 22 h to obtain a spherical metal catalytic material;

[0038] S3: Grind the spherical metal catalyst material and sieve it with a mesh size of 40, then take 0.5g of the sieved spherical metal catalyst material powder and 3.5g of hexadecyltrimethylammonium bromide and evenly disperse them in a mixed solvent of 700mL of ethanol and deionized water, the volume ratio of ethanol to deionized water is 3:4, then add 5g of 28wt% ammonia water to the dispersion, then react at room temperature for 25min, then add 1g of ethyl silicate to the reaction solution, react at room temperature for 5.5h, after the reaction, centrifuge the reaction solution, the centrifugal speed is 8000r / min, the centrifugal time is 6min, dry the solid after centrifugation at 80℃ for 30h, and then calcine at 480℃ for 2h to obtain Ni / Fe2O3@SiO2 core-shell catalyst I.

[0039] Example 3

[0040] An iron-silicon core-shell type hydrocracking catalyst, the preparation method of which comprises the following steps:

[0041] S1: Add 6g Fe(NO3)3, 3g ammonium molybdate and 52mL deionized water into a beaker, stir well, add 2.54g sodium acetate and 1.13g hexadecyltrimethylammonium bromide, then add 34mL ethylenediamine, stir well, transfer to a stainless steel autoclave with a polytetrafluoroethylene liner, and react at 220°C for 12h; after the reaction is completed, cool the autoclave to room temperature to obtain a red colloid;

[0042] S2: The red colloid is repeatedly washed with deionized water until it is neutral, and then the red colloid is centrifuged at a centrifugal speed of 8500 r / min for 6 min. The solid matter obtained after the centrifugation is then dried at 150° C. for 26 h to obtain a spherical metal catalytic material;

[0043] S3: Grind the spherical metal catalyst material and sieve it with a mesh size of 40, then take 1.5g of the sieved spherical metal catalyst material powder and 5.5g of hexadecyltrimethylammonium bromide and evenly disperse them in a mixed solvent of 1100mL of ethanol and deionized water, the volume ratio of ethanol to deionized water is 5:6, then add 15g of 28wt% ammonia water to the dispersion, then react at room temperature for 35min, then add 10g of ethyl silicate to the reaction solution, react at room temperature for 6.5h, after the reaction, centrifuge the reaction solution, the centrifugal speed is 8000r / min, the centrifugal time is 6min, dry the solid after centrifugation at 150℃ for 36h, and then calcine at 520℃ for 5h to obtain Mo / Fe2O3@SiO2 core-shell catalyst.

[0044] Example 4

[0045] An iron-silicon core-shell type hydrocracking catalyst, the preparation method of which comprises the following steps:

[0046] S1: Add 6g Fe(NO3)3·9H2O, 0.33g nickel nitrate and 90mL deionized water into a beaker, stir well, add 1.9g sodium acetate and 1g hexadecyltrimethylammonium bromide, then add 20mL ethylenediamine, stir well, transfer to a stainless steel autoclave with a polytetrafluoroethylene liner, and react at 200℃ for 10h; after the reaction is completed, cool the autoclave to room temperature to obtain a red colloid;

[0047] S2: repeatedly washing the red colloid with deionized water until it is neutral, then centrifuging the red colloid at a centrifugal speed of 8000 r / min for 5 min, and then drying the solid matter obtained after centrifugation at 100° C. for 24 h to obtain a spherical metal catalytic material;

[0048] S3: Grind the spherical metal catalyst material and sieve it with a mesh size of 40, then take 1g of the sieved spherical metal catalyst material powder and 5g of hexadecyltrimethylammonium bromide and evenly disperse them in a mixed solvent of 900mL of ethanol and deionized water, the volume ratio of ethanol to deionized water is 4:5, then add 10g of 28wt% ammonia water to the dispersion, then react at room temperature for 30min, then add 7g of ethyl silicate to the reaction solution, react at room temperature for 6h, after the reaction, centrifuge the reaction solution, the centrifugal speed is 8000r / min, the centrifugal time is 6min, dry the solid after centrifugation at 120℃ for 30h, and then calcine at 500℃ for 5h to obtain Ni / Fe2O3@SiO2 core-shell catalyst II.

[0049] Comparative Example 1

[0050] An iron-silicon core-shell type hydrocracking catalyst, the preparation method of which comprises the following steps:

[0051] S1: Add 6g Fe(NO3)3·9H2O and 70mL deionized water into a beaker, stir well, add 1.95g sodium acetate and 1g hexadecyltrimethylammonium bromide, then add 30mL ethylenediamine, stir well, transfer to a stainless steel autoclave with a polytetrafluoroethylene liner, and react at 200°C for 10h; after the reaction is completed, cool the autoclave to room temperature to obtain a red colloid;

[0052] S2: The red colloid was repeatedly washed with deionized water until it was neutral, and then the red colloid was centrifuged at a speed of 8000 r / min for 6 min. The solid matter obtained after centrifugation was dried at 100 ° C for 24 h to obtain a Fe2O3 spherical material;

[0053] S3: Grind the Fe2O3 spherical material and sieve it with a mesh size of 40, then take 1g of the sieved Fe2O3 spherical material powder and 4.5g of hexadecyltrimethylammonium bromide and evenly disperse them in a mixed solvent of 900mL of ethanol and deionized water, the volume ratio of ethanol to deionized water being 4:5, then add 10g of 28wt% ammonia water to the dispersion, then react at room temperature for 30min, then add 4g of ethyl silicate to the reaction solution, react at room temperature for 6h, after the reaction is completed, centrifuge the reaction solution at a centrifugal speed of 8000r / min and a centrifugal time of 6min, dry the solid after centrifugation at 100℃ for 24h, and then calcine at 500℃ for 5h to obtain Fe2O3@SiO2 core-shell catalyst.

[0054] Comparative Example 2

[0055] An iron-silicon core-shell type hydrocracking catalyst, the preparation method of which comprises the following steps:

[0056] S1: Add 6g Fe(NO3)3, 1g nickel nitrate and 71mL deionized water into a beaker, stir well, add 7.68g sodium acetate and 4.5g hexadecyltrimethylammonium bromide, then add 49mL ethylenediamine, stir well, transfer to a stainless steel autoclave with a polytetrafluoroethylene liner, and react at 180°C for 8h; after the reaction is completed, cool the autoclave to room temperature to obtain a red colloid;

[0057] S2: The red colloid is repeatedly washed with deionized water until it is neutral, and then the red colloid is centrifuged at a centrifugal speed of 7500 r / min for 5 min. The solid matter obtained after the centrifugation is then dried at 80° C. for 22 h to obtain a spherical metal catalytic material;

[0058] S3: Grind the spherical metal catalyst material and sieve it with a mesh size of 40, then take 0.5g of the sieved spherical metal catalyst material powder and 3.5g of hexadecyltrimethylammonium bromide and evenly disperse them in a mixed solvent of 700mL of ethanol and deionized water, the volume ratio of ethanol to deionized water is 3:4, then add 5g of 28wt% ammonia water to the dispersion, then react at room temperature for 25min, then add 15g of ethyl silicate to the reaction solution, react at room temperature for 5.5h, after the reaction is completed, centrifuge the reaction solution, the centrifugal speed is 8000r / min, the centrifugal time is 6min, dry the solid after centrifugation at 80℃ for 30h, and then roast at 480℃ for 2h.

[0059] Comparative Example 3

[0060] An iron-silicon core-shell type hydrocracking catalyst, the preparation method of which comprises the following steps:

[0061] S1: Add 6g Fe(NO3)3, 3g ammonium molybdate and 52mL deionized water into a beaker, stir well, add 2.54g sodium acetate and 1.13g hexadecyltrimethylammonium bromide, then add 34mL ethylenediamine, stir well, transfer to a stainless steel autoclave with a polytetrafluoroethylene liner, and react at 220°C for 12h; after the reaction is completed, cool the autoclave to room temperature to obtain a red colloid;

[0062] S2: The red colloid is repeatedly washed with deionized water until it is neutral, and then the red colloid is centrifuged at a centrifugal speed of 8500 r / min for 6 min. The solid matter obtained after the centrifugation is then dried at 150° C. for 26 h to obtain a spherical metal catalytic material;

[0063] S3: Grind the spherical metal catalyst material and sieve it with a mesh size of 40, then take 1.5g of the sieved spherical metal catalyst material powder and 5.5g of hexadecyltrimethylammonium bromide and evenly disperse them in a mixed solvent of 1100mL of ethanol and deionized water, and the volume ratio of ethanol to deionized water is 5:6, then add 15g of 28wt% ammonia water to the dispersion, and then react at room temperature for 35min, then add 0.5g of ethyl silicate to the reaction solution, and react at room temperature for 6.5h. After the reaction is completed, centrifuge the reaction solution at a centrifugal speed of 8000r / min and a centrifugal time of 6min. Dry the solid after centrifugation at 150℃ for 36h, and then roast at 520℃ for 5h.

[0064] The iron-silicon core-shell type hydrocracking catalysts prepared in the embodiments of the present invention have similar performances. Taking embodiments 1 to 3 as examples, the performances of related products are described.

[0065] Experimental example

[0066] ①Structural test

[0067] The catalysts prepared in Examples 1 to 3 were subjected to electron microscopy scanning, and the SEM images are as follows: Figures 1 to 3 shown.

[0068] ②Performance test

[0069] 40 g of vacuum residue oil (properties are shown in Table 1) was added to a 300 mL autoclave, and 1.2 g of the catalyst prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was added to each autoclave. The reaction pressure was 11 MPa, the reaction temperature was 430° C., and the reaction time was 3 h. After the reaction was completed, the temperature was reduced to room temperature, the pressure was released, the liquid oil was taken out and weighed, and the product was subjected to vacuum distillation using a vacuum distillation apparatus. The gasoline, naphtha, middle distillate oil, 350 to 520° C. fraction yield, liquid yield, gas yield and coke yield were separated by a boiling range cutting method. The experimental results are shown in Table 2.

[0070] Table 1 Vacuum residue properties

[0071] Analyze Project Test Results <![CDATA[Density (20 °C), Kg / m 3 > 985.5 Viscosity (100℃), cSt 84.7 Carbon residue value, wt.% 10.7 S, wt.% 3.1 Fe, ppm 11.9 Ni, ppm 46.2 V, ppm 111.6

[0072] Table 2 Distribution of vacuum residue suspension bed hydrocracking reaction products

[0073]

[0074]

[0075] It can be seen from the data in Table 2 that the heavy oil conversion rate of the residual oil suspension bed hydrocracking catalyst prepared by the method of the present invention can reach about 90%, and the total yield of naphtha and middle distillate oil is as high as about 60%. Compared with Comparative Example 1, the spherical metal material is doped with different transition metals in the embodiment, and then wrapped with a silicon shell. The effect of the catalyst after doping with metals is enhanced, the heavy oil conversion rate and the yield of naphtha and middle distillate oil in the residual oil suspension bed hydrocracking reaction are significantly increased, and the gas yield and coke yield are significantly reduced. Comparative Examples 2 and 3 found that adding different amounts of tetraethyl orthosilicate resulted in changes in the thickness of the silicon layer, and the catalyst residual oil conversion rate was reduced. Therefore, it can be seen from the above results that the iron silicon core-shell type hydrocracking catalyst of the present invention has higher catalytic activity, lower gas yield and coke yield, and has good application prospects in the residual oil suspension bed hydrocracking reaction process.

[0076] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.

Claims

1. A method for preparing an iron-silicon core-shell type hydrocracking catalyst, characterized in that: The following steps are involved: S1: mixing iron salt, VIB and / or VIII group transition metal salt, water, sodium acetate, hexadecyltrimethylammonium bromide and ethylenediamine to obtain a reaction solution, and reacting at 180-220° C. for 8-12 hours to obtain a colloid; S2: washing the colloid to neutrality, and obtaining a spherical metal catalytic material after centrifugation and drying; S3: Grind and sieve the spherical metal catalyst material, then evenly disperse the spherical metal catalyst material powder and hexadecyltrimethylammonium bromide in a solvent, add ammonia water, react at room temperature for 25 to 35 minutes, then add ethyl silicate to the reaction solution, react at room temperature for 5.5 to 6.5 hours, and after the reaction is completed, centrifuge, dry and calcine the reaction solution to obtain the product.

2. The method for preparing the iron-silicon core-shell type hydrocracking catalyst according to claim 1, characterized in that: The iron salt in step S1 is one or more of ferric nitrate, ferric chloride, ferric sulfate, ferric phosphate, ferric perchlorate, ferric nitrate nonahydrate and ferric chloride hexahydrate.

3. The method for preparing the iron silicon core-shell type hydrocracking catalyst according to claim 2, characterized in that: In step S1, the VIB group transition metal salt is ammonium molybdate and / or metatungstic acid; the VIII group transition metal salt is one or more of nickel nitrate, nickel sulfide and cobalt nitrate.

4. The method for preparing the iron-silicon core-shell type hydrocracking catalyst according to claim 3, characterized in that: The concentration of the iron salt in the reaction solution of step S1 is 50-70 g / L; the material-liquid ratio of the iron salt, VIB and / or VIII group transition metal salt, sodium acetate, hexadecyltrimethylammonium bromide and ethylenediamine is 3-8 mmol: 0.3-0.8 mmol: 7.5-10 mmol: 1 mmol: 4-11 mL.

5. The method for preparing the iron-silicon core-shell type hydrocracking catalyst according to claim 4, characterized in that: In step S2, the centrifugal speed is 7500-8500 r / min, the centrifugal time is 5-6 min; the drying temperature is 80-150° C., and the drying time is 22-26 h.

6. The method for preparing the iron-silicon core-shell type hydrocracking catalyst according to claim 5, characterized in that: The particle size of the spherical metal catalyst material powder is not less than 40 meshes; the solvent is a mixed solvent of ethanol and water, and the volume ratio of ethanol to water in the mixed solvent is 3-5:4-6; the concentration of ammonia water is 28wt%.

7. The method for preparing the iron-silicon core-shell type hydrocracking catalyst according to claim 6, characterized in that: In step S3, the material-liquid ratio of the spherical metal catalyst material powder, hexadecyltrimethylammonium bromide, solvent, ammonia water and ethyl silicate is 0.5-1.5 g: 3.5-5.5 g: 700-1100 mL: 5-15 g: 1-10 g.

8. The method for preparing the iron-silicon core-shell type hydrocracking catalyst according to claim 7, characterized in that: In step S3, the drying temperature is 80-150° C., and the drying time is 24-36 hours; the roasting temperature is 480-520° C., and the roasting time is 2-5 hours.

9. The iron-silicon core-shell type hydrocracking catalyst prepared by the method for preparing the iron-silicon core-shell type hydrocracking catalyst according to any one of claims 1 to 8.

10. Use of the iron-silicon core-shell type hydrocracking catalyst according to claim 9 in a residual oil suspension bed hydroconversion process.